Dream content influences daily spirituality - John Balch; John Balch; George Hodulik; Rachel Raider; Aidan David; Chanel Reed; Wesley J. Wildman; Wesley J. Wildman; Wesley J. Wildman; David Rohr; Patrick McNamara; Patrick McNamara; et al. (Frontiers in Psychology, 2025)
IntroductionThe daily effects of supernatural-agent (SA) concepts on spirituality remain poorly understood. In this study, we focused on dreaming as an avenue to study the effect of SA concepts on spirituality. This work contributes to a long history of research linking together dreaming and spirituality by utilizing quantitative and longitudinal methods.MethodsWe conducted an intensive longitudinal study of sleep and dreaming among N = 124 healthy adults over 2 weeks, with N = 61 wearing the Dreem 3 EEG headband to measure sleep architecture We collected dream reports and assessed supernatural content, dream affect, and dreamer agency. Linear mixed effects modeling examined relationships between dream variables and daily spirituality measures To evaluate our time-series data, we constructed a temporal neural network (TSANN) to test causal lagged relationships between our dream predictors and daily spirituality measures.ResultsDreams containing supernatural content were associated with reduced dreamer agency and more negative affect, and were rated as more bizarre, strange, and scary. Mixed effects models demonstrated that dream affect and REM sleep percentage significantly predicted next-day closeness-to-God ratings and authoritarian God concepts when controlled for participant variance in trait spirituality, as well as effects at a 4-day lag for dream agency and dream affect. The neural network analysis established causal support for the lagged closeness-to-God mixed effects models, with saliency maps showing that 3-4 day lagged predictors influenced model outputs more than 1–2 day lags, demonstrating the importance of multi-day effects in measuring the impact of dream variables on daily closeness-to-God ratings.DiscussionThese findings indicate that SA concepts in dreams contribute to daily levels of spirituality both the following day and with a multi-day lag. We conclude that dreams thus represent a key pathway for the influence of SA concepts on spirituality, and provide a valuable area of study for future research in the psychology of religion.